Skeletal muscle oxygen delivery in heart failure and breast cancer: mechanisms and therapeutic insights - Weber, Ramona Elaine (My University, 2025)
The onset of exercise requires precise cardiovascular adjustments to ensure adequate skeletal muscle oxygen delivery (Q̇O₂) to meet the metabolic demands (V̇O₂) of contractions. A hallmark of exercise intolerance is reduced nitric oxide (NO) bioavailability (e.g. endothelial dysfunction) and Q̇O₂-to-V̇O₂ mismatch that effectively reduces the partial pressure gradient for O₂ diffusion across the interstitial space (PO₂is) and disrupts the intracellular milieu. This presents significant quandaries for individuals diagnosed with heart failure (HF) and breast cancer (BC), both of which are malignancies associated with O₂ transport dysfunction and are compounded with limited therapeutic options available to support exercise tolerance. With this, Chapter 2 examines the effects of targeting downstream of NO dysfunction (via soluble guanylyl cyclase (sGC) stimulator) to improve vascular NO-sensitivity, exercise tolerance and PO₂is during contractions in HF rats. Evidence suggests that there is a bi-directional relationship between HF and BC, with each condition predisposing individuals to the other. While in HF, central O₂ transport dysfunction largely precedes and promotes O₂ transport limitations, BC, as an isolated condition, does not directly impact cardiac function. Therefore, in Chapter 3 we investigated the impact of tumor-bearing alone on maximal O₂ uptake during exercise (V̇O₂max) in BC rats. Despite no change in V̇O₂max before and after tumor growth, tumor-bearing BC rats had a reduced exercise economy, suggesting that peripheral O₂ transport limitations likely have a role in limiting sustained exercise performance. In Chapter 4, we measured the resting and contracting PO₂is in BC rats and to what extent NO-signaling has in control over PO₂is kinetics. We found that BC rats displayed decreased endothelium-independent vasodilation coupled with an increased reliance on basal NO production in comparison to healthy controls. Collectively, these findings highlight the critical role that NO has in regulating Q̇O₂-to-V̇O₂ matching in both HF and BC.
Keywords: Exercise; Skeletal muscle; Breast cancer; Nitric oxide; Microcirculation; Oxygen transport